Empowering Vulnerable Populations through Technology: Innovations and Challenges in Social Work - PHAM, Minh Khang; NHAN, Thi Lac An; VUONG, Nguyen Toan Thien; NGUYEN, Mai Bao Thy; NGUYEN, Phuong Nam; SANDIRAMOURTY, Shridevi; NGUYEN, Thi Tu Uyen; PHAM, Ngoc Gia Bao; NGUYEN, Truong Thanh Hai (Journal of Research in Educational Sciences; Vol 15 No 1 (2024): JRES, Volume XV, Issue 1(17), Summer 2024DO - 10.14505/jres.v15.1(17).01, 2024)
Purpose: This study aims to explore the efficacy of integrating digital solutions and technological aids in social work practices, specifically for assisting vulnerable populations. It investigates the historical and current relevance of technology in social work, with a focus on overcoming the digital divide that restricts access for these groups. Methodology: Utilizing a mixed-methods approach, this research combines qualitative and quantitative methodologies, including surveys, interviews, and observational studies, to examine the advantages and limitations of digital interventions like telehealth platforms compared to traditional face-to-face services. Additionally, it delves into the potential of Artificial Intelligence (AI) and related technologies to foster independence among vulnerable populations. Findings: The study reveals that while digital solutions offer significant benefits, including increased accessibility and potential for personalization through AI, they also present challenges, notably the digital divide due to economic, cognitive, and socio-cultural barriers. It suggests that hybrid models incorporating both digital and traditional methods could enhance social work practices. The research underscores the importance of addressing ethical considerations in the deployment of AI technologies. Originality: This research contributes original insights into the integration of technology within social work, highlighting the complexities of the digital divide and proposing a strategic framework for incorporating technological aids. It offers a foundational understanding of how digital tools can complement traditional social work practices, ensuring ethical considerations are prioritized. Furthermore, it opens avenues for future research on the dynamic interplay between technology and social work, aiming for a more inclusive and effective approach to supporting vulnerable populations.